Normative Criticism of the Local Government Internal Control System Based on The Principles of State Financial Management to Realize Good Governance - Novemyanto, Alfin Dwi (Public Policy and Management Inquiry, 2025)
The high weakness of the Local Government Internal Control System (SPI) as identified in the 2023 Local Government Financial Report (LKPD), which shows 5,426 findings of structural, procedural and functional weaknesses. This research examines SPI normatively within the framework of the principles of state financial management, in order to assess the extent to which SPI is able to guarantee the principles of good governance which include legality, accountability, transparency, efficiency, and effectiveness. The research method is normative legal research with statutory and conceptual approaches, using qualitative analysis methods based on systematic, grammatical, and teleological interpretations as developed by Peter Mahmud Marzuki. The results show that SPI weaknesses not only have administrative impacts, but are also a form of violation of imperative legal norms governing public financial management. SPI that fails to perform the internal control function substantively has implications for systemic damage to fiscal governance and violations of constitutional principles. The novelty of this research lies in the meaning of SPI as a legal instrument guarding principles, not just an administrative tool, and its contribution in formulating a valuebased internal control model based on legal principles to build a legal, accountable and democratic regional financial system.